Beep beep beep, ano ang sabi ng jeep? stories of PUJ drivers in Iloilo City during the COVID-19 pandemic Kiara Marie B. Avelino and Ma. Ysabelle M. Felix. - Avelino, Kiara Marie B.
This qualitative study focused on the narratives of Public Utility Jeepney (PUJ) drivers who operated within Iloilo City before and during the COVID-19 pandemic. Seven (7) PUJ drivers who have at least five (5) years of experience as a PUJ driver and consider driving PUJs as their main source of income during the COVID-19 pandemic were recruited from different Jeepney Owners and Drivers' Associations (JODRAs) in Iloilo City. An in-depth semi-structured interview was conducted with the PUJ drivers and two key informants. Open-ended questions were used which were then recorded and transcribed verbatim. The narratives of the PUJ drivers were analyzed using Narrative Thematic Analysis. The results of this study provided insights into the experiences of PUJ drivers, including the challenges they faced during the COVID-19 pandemic, their coping strategies, and the lessons learned from the experiences. The drivers encountered various challenges, such as financial hardship, physical and mental health concerns, and uncertainty about the future. To cope with the stress, they employed diverse strategies, such as seeking support from their networks, relying on religion and spirituality, distracting themselves, embracing their reality, and in some cases, denying the existence of the pandemic. The significance of social support, financial preparedness, awareness, and readiness for future crises was also emphasized. With these findings, the recommendation include access to healthcare and well-being, economic support and financial resilience, social support networks, comparative studies, and further research on the long-term impacts of COVID-19. Keywords: PUJ drivers, Narratives, Narrative Thematic Analysis, COVID-19 pandemic, Public Transportation